Safety and Efficacy of Endovascular Therapy for Blood Blister-Like Aneurysms: Willis Covered Stents and Double Stents Assistant Coils—A Single Center Cohort Study - Chang, Hanxiao; Shen, Yuqi; Li, Zheng; Lin, Chao; Chen, Hua; Lu, Hua (Frontiers in Neurology, 2021)
Objective: To summarize and discuss the application of Willis covered stents (WCSs) and double stent-assisted coils in the treatment of blood blister-like aneurysms (BBAs). Materials and Methods: Thirty-two patients with BBAs treated from January 2015 to October 2020 were included in the study. Among them, 18 were treated using WCSs and 14 using double stents-assisted coils. The indications for treatment, perioperative findings, and postoperative follow-up results were collected and analyzed. Results: All 32 patients had successful stent deployments. Complete aneurysm occlusion was achieved in all 18 patients treated with WCSs immediately. WCS-related adverse events included 2 cases of mild vasospasm and 4 aggressive procedure-related vasospasms during WCS deployment, a case of dissection after WCS deployment, and 1 death due to ipsilateral temporal lobe rebleeding at the sixth day after WCS deployment. In patients treated with double stent-assisted coils, there were 3 cases of neck remnants, 1 acute occlusion of the ipsilateral MCA branch, and 4 mild procedure-related intraoperative vasospasms. The mean follow-up period was 4.2±1.6 months (range 3–6 months). Follow-up imaging data were available for 25 patients (78.1%). In the first postoperative angiographic follow-up, all BBAs were completely occluded. Mild asymptomatic stent stenosis was observed in 3 patients treated with WCSs. Follow-up examination at 6 months after the employment of WCSs showed that the modified Rankin score (mRs) was 0 in 6 patients, 1 in 5 patients, 2 in 3 patients, 3 in 1 patient, 4 in 2 patients, and 6 in 1 patient. After treatment with double stents-assisted coils, the mRs was 0 in 4 patients, 1 in 5 patients, 2 in 3 patients, and 4 in 2 patients. Conclusions: WCSs and double stent-assisted coils for the treatment of BBAs are both safe and efficient. WCSs provide a higher rate of immediate occlusion; however, there was no significant difference in the long term.